(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
The theme of sexuality in old age is full of prejudice, stigmatization and discrimination, coming from the most diverse social sectors. This allocation of desexualization given by social ideology to the geriatric population contributes greatly to the misinformation about safe sexual practice by this group. From this perspective, the 2019 DATASUS data reflect this scenario by mentioning that around 1059 deaths of individuals belonging to the elderly population were recorded, among the 7773 deaths caused by complications arising from HIV infection. Therefore, in view of these data, it is increasingly necessary to carry out actions aimed at health promotion and education for the elderly. With this objective, based on the experiences of medical students with the elderly in the group “Idosos da Alegria de Viver”, through the application of the Sexuality in the Third Age questionnaire and the distribution of booklets that addressed the main points about the virus HIV and AIDS it was possible to implement these educational actions for this public data. In this way, through dialogue and active listening of the research participants, the students were able to extract that about half of the interviewees expressed not knowing how to proceed with a possible HIV infection and not knowing about pre-exposure prophylaxis to HIV, thus demonstrating the gaps present in the health area. Therefore, with the participation of academics in the research project, it was possible for the student to experience the implementation of educational actions in health for the target audience, in order to contribute to the improvement of the doctor-patient relationship and more humanized active listening as well as the intergenerational dialogue of physicians under construction with their future patients. In this way, the voices of elderly people who were veiled began to be heard by everyone, including health professionals, whether during training or after training, because every human being has the right to be heard.